THE INFLUENCE OF BRAND IMAGE AND COUNTRY OF ORIGIN ON PURCHASE DECISION OF OPPO SMARTPHONE IN MANADO - Kausuhe, Jutresia Nigita; Worang, Frederik G.; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
In this development era, all things continue to develop, especially the technologies that sophisticated increase, including communication technology, which is currently growing rapidly. In the development of communication technology, Smartphone is a development form of Handphone that has various advantages and make smartphone becomes the favorite of many people, including people in Indonesia. A large number of smartphone users has led to the emergence of many smartphone brands in Indonesia that are competing to attract the attention of smartphone enthusiasts, and one of the smartphone brands is Oppo. The purpose of this study is to find out whether The Influence of Brand Image and Country of Origin on Purchase Decision of Oppo Smartphone In Manado. This research implies a quantitative method, To achieve this goal the researchers distributed questionnaires and samples used 100 respondents. The results of this study found that brand image has a significant positive effect on customer loyalty while the country of origin has a positive but not significant effect on the purchase decision.Â Keywords:brand image, country of origin, purchase decision